The Giant SALR Cluster Fluid: A Review. Issue 7 (25th April 2019) - Sweatman, Martin B.; Lue, Leo
Abstract: Recent developments in understanding the behavior of equilibrium fluids with competing short‐range attractions and long‐range repulsions at low concentration are reviewed. Typically, this SALR model system is used to represent solutions where at least one of the solute species interacts via a screened‐Coulomb potential, which includes many colloidal, nanoparticle, and polyelectrolyte solutions among others. Provided neither the short‐range nor long‐range interactions are too strong, and the concentration remains sufficiently low, discrete spherical clusters of solute are expected, here called "Giant SALR clusters." Because these clusters can themselves be disordered, as though fluid particles with a renormalized interaction, such cluster fluids cannot be treated using standard mean field methods. This review therefore focuses on theoretical routes that aim to overcome this difficulty. The main outcomes of these theories are highlighted and their application to soft matter and especially biology, including complex coacervates, membraneless organelles, and the origin of life is discussed. Abstract : Solutes that become charged in solution can form disordered dispersions of giant SALR clusters under suitable conditions. Theoretical methods used to model their equilibrium behavior, which is thought to be relevant to many important soft matter and biological systems such as complex coacervates and membraneless organelles, are reviewed.